Worldwide arthroplasty research productivity and contribution of Turkey - Bilgehan Çatal; Yunus Emre Akman; Erhan Şükür; İbrahim Azboy (Acta Orthopaedica et Traumatologica Turcica, 2018)
Purpose: Bibliometrics is increasingly used to assess the quantity and quality of scientific research output in many research fields worldwide. However, to the best of our knowledge, no studies have documented the main characteristics of arthroplasty publications from different countries. This study aimed to evaluate the worldwide research productivity and status of Turkey in the field of arthroplasty using bibliometric methods and to provide an insight into the arthroplasty research for surgeons and researchers. Methods: The Web of Science database was searched to identify arthroplasty articles published between 2006 and 2016. The contributions of countries were evaluated based on publication count, citation average, h-index and publication rate in the top 10 ranked journals. Each countries publication output was adjusted according to population size. Results: A total of 26.167 articles were identified. World arthroplasty publications were increased significantly over time (p < .005). The United States was the most productive country with 9007 articles (34,4% of total) followed by England with 2939 articles (11,4 of total) and Germany with 1881 articles (7,1% of total). According to average citations per item, Scotland was in the first place followed by Denmark and Sweden, whereas in the first place according to publication output adjusted by population size was Switzerland followed by Denmark and Scotland. The United States was also in the first place according to h-index and publication rate in the top 10 ranked journals. Founding average was 28,8% (7539 of 26164) for the arthroplasty articles that were analyzed in the study. Conclusion: There is a rapid increase in the number of articles in arthroplasty research from 2006 to 2016. The United States was the most productive country as measured by total publications in the arthroplasty field. However, some small European countries with high in-come have higher quality of articles and better productivity when adjusted for population. Gross domestic product (GDP) per capita and research foundation had positive affect on arthroplasty publications, both qualitatively and quantitatively. Keywords: arthroplasty, bibliometric analysis, productivity, research, worldwide